(untitled) (Eurasian Journal of Philology Science and Education, 2018)
Introduction of English as one of obligatory languages side by side with Kazakh and Russian into an educational program of schools and universities is a very complex undertaking not only from an educational point of view, but from cultural and social point of view as well. There is certain resistance and misunderstanding on the part of different individuals. Realization of the project on introduction of English as the medium of instruction for four subjects: biology, chemistry, informatics and physics will not happen in one day and it will not end. There must be a thorough preparatory work which includes various stages like developing textbooks in mainstream subjects, improving English language proficiency of teachers as well as of school children and university students. All that work demands significant financial investments.